Structure-based design of potent and selective inhibitors targeting RIPK3 for eliminating on-target toxicity in vitro - Haixia Su; Guofeng Chen; Hang Xie; Wanchen Li; Muya Xiong; Jian He; Hangchen Hu; Wenfeng Zhao; Qiang Shao; Minjun Li; Qiang Zhao; Yechun Xu (Nature Communications)
Abstract The essential role of RIPK3 in necroptosis makes its inhibition a promising therapeutic strategy. However, the development of RIPK3 inhibitors has been hampered by on-target apoptosis and limited kinase selectivity. Inspired by the R69H mutation, which prevents on-target apoptosis by disrupting RIPK3 dimerization, we design LK-series inhibitors that effectively inhibit RIPK3 in biochemical assays and block TNF-α-induced necroptosis in both mouse L929 and human HT29 cells without inducing apoptosis. The representative compound, LK01003, shows high selectivity across a panel of 379 kinases. Our structural studies reveal that LK compounds act as Type I1/2 inhibitors, engaging a unique hydrophobic site and stabilizing an inactive conformation of RIPK3. Moreover, several type II inhibitors are also revealed to maintain RIPK3 in the inactive conformation and do not induce on-target apoptosis. These findings suggest a promising strategy for rational design of safe and selective inhibitors by locking the inactive conformation of RIPK3.